Frontiers of manufacturing science and measuring technology II : selected, peer reviewed papers from the 2012 2nd International Conference on Frontiers of Manufacturing Science and Measuring Technology (ICFMM2012), June 12-13, 2011, Xi'an, China - Sung, Wen-Pei; Kao, Jimmy C. M. (Jimmy Chih-Ming), 1963-; Chen, Ran (Advanced materials research ;, 2012)
This book brings together 389 pieces of peer- This book brings together 389 peer-reviewed papers on Manufacturing Science and Measuring Technology. It provides the reader with a broad overview of the latest advances in the field of manufacturing science and measuring technology. It is divided into: Chapter 1: Manufacturing and Design Science; Chapter 2: Materials Science and Engineering; Chapter 3: Measuring Technology and Mechatronics. Review from Book News Inc. Some 400 papers, selected from more than twice that many submissions, look at manufacturing and design science, materials science an.